Improved mechanical properties of beta-tricalcium phosphate by addition of akermanite and 45S5 bioglass. (May 2014) - Shuai, C.; Yang, B.; Peng, S.; Min, A.
Abstract : Beta-tricalcium phosphate ceramics [beta-TCP, Ca3 (PO4)2 ] with enhanced mechanical properties were fabricated by liquid phase sintered at 1150°C for 3 h using the additives of akermanite and 45S5 bioglass (A4BG). Preliminary study showed that A4BG-10 composed of 10 wt-% akermanite and 90 wt-% 45S5 bioglass has a melting temperature of 1150°C, which is in the range of the sintering temperature of beta-TCP. Then, A4BG-10 was added into beta-TCP to provide liquid phase for improving mechanical properties. The results showed that the bending strength, compressive strength, compressive modulus and fracture toughness increased by 97·1, 167, 139 and 64% respectively, with the content of A4BG-10 up to 5 wt-%. It was attributed to the increase in compactness due to the decrease in the number of the pores, while the mechanical properties decreased with the further increase in A4BG-10, owing to the occurrence of cracks induced by the thermal stress.